Report from the 2nd Cardiovascular Outcome Trial (CVOT) Summit of the Diabetes and Cardiovascular Disease (D&CVD) EASD Study Group - Schnell, Oliver; Standl, Eberhard; Catrinoiu, Doina; Genovese, Stefano; Lalic, Nebojsa; Skra, Jan; Valensi, Paul; Rahelic, Dario; Ceriello, Antonio (Cardiovascular diabetology, 2017)
The 2nd Cardiovascular Outcome Trial (CVOT) Summit of the Diabetes and Cardiovascular Disease (D&CVD) EASD Study Group was held on the 20th-21st October 2016 in Munich. This second Summit was organized in light of recently published CVOTs on diabetes, with the aim of serving as a reference meeting for discussion on this topic. Along with presentations on the results of the most recently published CVOTs, panel discussions on trial implications for reimbursement and the perspective of cardiologists and/or nephrologists, as well as on CVOTs weaknesses and potentials constituted the heart of the program. Future activities of the D&CVD EASD Study Group in 2017 include an annual meeting in Milano and the 3rd CVOT Summit on Diabetes of the D&CVD EASD Study Group, in Munich ( http://www.dcvd.org ).
Keywords: náklady na léky; kardiovaskulární nemoci; Humans; ochranné faktory; Drug Costs; rizikové faktory; výsledek terapie; Protective Factors; lidé; Diabetes Mellitus, Type 2; medicína založená na důkazech; Hypoglycemic Agents; Cardiovascular Diseases; Treatment Outcome; klinické zkoušky jako téma; hypoglykemika; Insurance, Health, Reimbursement; Clinical Trials as Topic; úhrada zdravotního pojištění; Risk Assessment; diabetes mellitus 2. typu; hodnocení rizik; Evidence-Based Medicine; Risk Factors